2019
DOI: 10.1155/2019/6342104
|View full text |Cite
|
Sign up to set email alerts
|

BA6 Induces Apoptosis via Stimulation of Reactive Oxygen Species and Inhibition of Oxidative Phosphorylation in Human Lung Cancer Cells

Abstract: Lung cancer is the leading cause of cancer deaths in the world, with a five-year survival rate of less than 30%. Clinically effective chemotherapeutic treatments at the initial stage may eventually face the dilemma of no drug being effective due to drug resistance; therefore, finding new effective drugs for lung cancer treatment is a necessary and important issue. Compounds capable of further increasing the oxidative stress of cancer cells are considered to have anticancer potential because they possessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…A recent study highlighted that oxidative stress or ROS formation is a critical factor of the stimuli that trigger ER stress-mediated apoptosis (48). The ROS-based ER stress pathway initiates intracellular Ca 2+ release via mitochondrial depolarization to manifest apoptosis induction (49). Consistently, our results indicated that AITC treatment increased ROS generation and the antioxidant NAC exhibited a protective effect against AITC.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study highlighted that oxidative stress or ROS formation is a critical factor of the stimuli that trigger ER stress-mediated apoptosis (48). The ROS-based ER stress pathway initiates intracellular Ca 2+ release via mitochondrial depolarization to manifest apoptosis induction (49). Consistently, our results indicated that AITC treatment increased ROS generation and the antioxidant NAC exhibited a protective effect against AITC.…”
Section: Discussionsupporting
confidence: 83%
“…Heteronemin is a spongean sesterterpenoid, which acts against different kinds of cancers [2,3] with low or non-cytotoxicity to non-malignant cells [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Heteronemin is a spongean sesterterpenoid, which acts against different kinds of cancers [ 2 , 3 ] with low or non-cytotoxicity to non-malignant cells [ 4 , 5 ]. Heteronemin potently inhibits anchorage-independent growth of human prostate cancer cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…ATP concentration assay. MG63 cells were seeded in triplicate at a density of 2 × 10 5 cells/well in six-well plates and then treated with various concentrations of piscidin-1 for 24 h. The cells were harvested in a lysis buffer (20 mM glycine, 50 mM MgSO4, and 4 mM ethylenediaminetetraacetic acid) 53 . ATP was measured using the ATP Colorimetric/Fluorometric Assay kit (BioVision, Inc., Milpitas, CA, USA) according to the manufacturer's instructions.…”
mentioning
confidence: 99%